An Improved Tobacco Mosaic Virus (TMV)-Conjugated Multiantigen Subunit Vaccine Against Respiratory Tularemia - Mansour, Ahd A.; Banik, Sukalyani; Suresh, Ragavan V.; Kaur, Hardeep; Malik, Meenakshi; McCormick, Alison A.; Bakshi, Chandra S. (Frontiers in Microbiology, 2018)
Francisella tularensis, the causative agent of the fatal human disease known as tularemia is classified as a Category A Select Agent by the Centers for Disease Control. No licensed vaccine is currently available for prevention of tularemia in the United States. Previously, we published that a tri-antigen tobacco mosaic virus (TMV) vaccine confers 50% protection in immunized mice against respiratory tularemia caused by F. tularensis. In this study, we refined the TMV-vaccine formulation to improve the level of protection in immunized C57BL/6 mice against respiratory tularemia. We developed a tetra-antigen vaccine by conjugating OmpA, DnaK, Tul4, and SucB proteins of Francisella to TMV. CpG was also included in the vaccine formulation as an adjuvant. Primary intranasal (i.n.) immunization followed by two booster immunizations with the tetra-antigen TMV vaccine protected 100% mice against i.n. 10LD100 challenges dose of F. tularensis live vaccine strain (LVS). Mice receiving three immunization doses of tetra-antigen TMV vaccine showed only transient body weight loss, cleared the infection rapidly, and showed minimal histopathological lesions in lungs, liver, and spleen following a lethal respiratory challenge with F. tularensis LVS. Mice immunized with the tetra-antigen TMV vaccine also induced strong ex vivo recall responses and were protected against a lethal challenge as late as 163 days post-primary immunization. Three immunization with the tetra-antigen TMV vaccine also induced a stronger humoral immune response predominated by IgG1, IgG2b, and IgG2c antibodies than mice receiving only a single or two immunizations. Remarkably, a single dose protected 40% of mice, while two doses protected 80% of mice from lethal pathogen challenge. Immunization of Interferon-gamma (IFN-γ)-deficient mice with the tetra-antigen TMV vaccine demonstrated an absolute requirement of IFN-γ for the generation of protective immune response against a lethal respiratory challenge with F. tularensis LVS. Collectively, this study further demonstrates the feasibility of TMV as an efficient platform for the delivery of multiple F. tularensis antigens and that tetra-antigen TMV vaccine formulation provides complete protection, and induces long-lasting protective and memory immune responses against respiratory tularemia caused by F. tularensis LVS.